Prevalence of deviations in hematological and biochemical parameters in patients with Delirium Tremens - Parbalkar, Ashana; Deshmukh, Rohit; Kale, Sanjiv S. (Nepal Journal of Neuroscience, 2024)
Introduction: Delirium Tremens (DTs) is an acute and severe form of alcohol withdrawal which if left untreated could lead to significant mortality. Identification of parameters which may lead to the progression of alcohol withdrawal to delirium tremens will aid in early initiation of appropriate treatment which in turn may help reduce the mortality rates. This study was undertaken to assess the prevalence of haematological and biochemical deviations in Delirium tremens and to assess the corelation between these deviations and severity of delirium tremens. Materials and Methods: A cross-sectional research was carried out at a Tertiary Care Centre over 6 months. Confusion Assessment Method (CAM) tool was applied as a delirium screening tool for patient selection. After gaining consent, 89 patients who met the criteria for inclusion were enrolled. Demographic and clinical data of the patient was collected and laboratory investigations were recorded. Delirium Index (DI) was applied in conjunction with the Modified Mini-Mental State (3MS) Test as a cognitive screening tool. SPSS-PC -25 version was used for data analysis. The Shapiro-Wilk test was used to investigate normal distribution. The difference in means between the groups was investigated using student t-test or Mann-Whitney U-test. Qualitative data were expressed in frequency and percentage. Spearman correlation coefficient was used to see correlation between different quantitative parameters. Statistics were deemed significant at a P <0.05. Results: Male gender, older age, unemployment, anemia, thrombocytopenia, hyponatremia, hyperbilirubinemia and raised SGOT were identified as potential risk factors for developing Delirium tremens. Anemia, hyponatremia, hyperbilirubinemia, and raised SGOT and ALP levels were identified as potential risk factors for worsening the severity of delirium Conclusions: Assessment of demographic details and deviations in laboratory parameters helps in identification of risk factors for developing Delirium tremens aiding in early intervention which prevents the worsening of the severity of delirium.